2018
DOI: 10.1097/nne.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Test Development, Administration, and Analysis

Abstract: Developing valid and reliable test items is a critical skill for nursing faculty. This research analyzed the test item writing practice of 674 nursing faculty. Relationships between faculty characteristics and their test item writing practices were analyzed. Findings reveal variability in practice and a gap in implementation of evidence-based standards when developing and evaluating teacher-made examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In addition, the study also reported that 57% of the respondents used 1 type of item analysis, with the point biserial as the most reported. 15 National nursing examinations such as the NCLEX-RN readily admit to using examination standards to assess item and examination analysis. The study results indicate that the participants lack the ability to effectively review and validate items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study also reported that 57% of the respondents used 1 type of item analysis, with the point biserial as the most reported. 15 National nursing examinations such as the NCLEX-RN readily admit to using examination standards to assess item and examination analysis. The study results indicate that the participants lack the ability to effectively review and validate items.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that education improves the quality of MCQs developed by teaching faculty and provides reassurance of reliability of examination items and accuracy of test scores. 5,14,15 Despite the problematic nature of item writing, there are some tools available to nursing faculty. Given the high stakes nature of these examinations, NCSBN provides a test plan to guide examinees.…”
mentioning
confidence: 99%
“…Fairness is based on the use of unbiased, reliable, and valid test questions, which from a positivist point of view provide an objective measurement of learning. 13,28 Instead E26 ADVANCES IN NURSING SCIENCE/JANUARY-MARCH 2022 of considering a student's context when enforcing these rules, educators operating from a positivist paradigm believe that treating everyone the same is fair. In this section, we briefly illustrate how traditional views of "fairness" lead to unfair and unjust treatment that creates inequity and suggest a solution to this problem.…”
Section: Equity In Nursing Education Through Universal Design For Lea...mentioning
confidence: 99%
“…However, nurse educators often strive for objectivity and fairness during examinations by using traditional face-to-face, proctored, timelimited examinations with multiple-choice and alternate format questions to emulate entry-to-practice examinations. 13 The goal of this type of testing is to measure learning by assigning a number to reflect and rank student abilities. 12 To understand why testing is designed in this way, we turn toward the philosophical basis for testing.…”
Section: Philosophical Foundations Of Traditional Examinationsmentioning
confidence: 99%
“…Peer review is considered a best practice when writing test items, 7 but the practice is underutilized by nursing faculty. 8,9 Nursing faculty, who are writing their own NGN items or choosing questions to include on classroom tests from vendor test banks, may not be able to undertake the same extensive review process used by the NCSBN. However, it is possible to follow item writing procedures similar to those used by the NCSBN and conduct peer review.…”
mentioning
confidence: 99%